Data from: Freezer on, lights off! Environmental effects on activity rhythms of fish in the Arctic - Hawley, Kate L.; Rosten, Carolyn M.; Haugen, Thrond O.; Christensen, Guttorm; Lucas, Martyn C. (Zenodo, 2017)
Polar regions are characterized by acute seasonal changes in the environment, with organisms inhabiting these regions lacking diel photoperiodic information for parts of the year. We present, to our knowledge, the first high-resolution analysis of diel and seasonal activity of free-living fishes in polar waters (74°N), subject to extreme variation in photoperiod, temperature and food availability. Using biotelemetry, we tracked two sympatric ecomorphs of lake-dwelling Arctic charr (Salvelinus alpinus n = 23) over an annual cycle. Charr activity rhythms reflected the above-surface photoperiod (including under ice), with diel rhythms of activity observed. During the dark winter solstice period, charr activity became arrhythmic and much reduced, even though estimated light levels were within those at which charr can feed. When twilight resumed, charr activity ensued as diel vertical migration, which continued throughout spring and with increasing day length, despite stable water temperatures. Diel activity rhythms ceased during the polar day, with a sharp increase in arrhythmic fish activity occurring at ice-break. Despite contrasting resource use, circannual rhythms were mirrored in the two ecomorphs, although individual variability in activity rhythms was evident. Our data support conclusions of functionally adaptive periods of arrhythmicity in polar animals, suggesting maintenance of a circannual oscillator for scheduling seasonal behavioural and developmental processes. Photoperiod_Dyrad Tracking data of 23 individual Arctic charr, from Lake Ellasjøen, Bear Island, Norway. Data is derived by biotelemetry from Sep 2009- Aug 2010.